(untitled) (Proceedings of the World Conference on Waste Management, 2019)
India will be producing 80-85 MT of Solid waste by 2030. Given the alarming quantity it is imperative to bring in methods which will alleviate the problem especially the plastic waste. One of the products which helps in effective disposal of plastics is the Reverse Vending Machine (RVM). An RVM is a device which accepts bar coded plastic bottles and returns digital cash or redeemable coupons. The field study and literature show that reverse vending machine is not used extensively. This study attempts to explore the challenges for adoption of eco-friendly products like RVM. A conceptual model was built using the variables identified through literature review. The variables identified included awareness, willingness, incentives, convenience and involvement. A survey was designed and data was collected from 246 citizens to understand their views. Structural Equation Modelling was used to test conceptual model. The results emphatically show that willingness to adopt RVM was influenced by factors of involvement, convenience, awareness and incentives in that order. It is also intuitive that when involvement is high then there is an attempt to become aware and adopt eco-friendly methods which is reiterated by the results. Hence citizens have to get involved either by their own interest or by enforcing through legislation and policies to use RVM. The study concludes by recommending more policies and strategies like “bottle bill”, “European Union Plastic Strategy” and Recycle Refund Systems to be mandated across the world to encourage citizens to use methods which will keep our environment plastic free.